Planning and managing a COVID‐19 mobile testing site - Rahn, Josh (Campus Security Report, 2020)
The State University of New York at Albany is contributing to the battle against COVID‐19 in numerous ways, from donations of personal protective equipment to the 3D printing of protective face shields.